2009
DOI: 10.1152/ajpgi.90583.2008
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin-6 protects against mitochondrial dysfunction and liver injury during ischemia-reperfusion in mice

Abstract: Hepatic ischemia-reperfusion (I/R) injury is an important complication of liver surgery and transplantation. Mitochondrial function is central to this injury. To examine alterations in mitochondrial function during I/R, we assessed the mitochondrial proteome in C57Bl/6 mice. Proteomic analysis of liver mitochondria revealed 234 proteins with significantly altered expression after I/R. From these, 13 proteins with the greatest expression differences were identified. One of these proteins, peroxiredoxin-6 (Prdx6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 47 publications
7
108
0
Order By: Relevance
“…2/2 mice linked to a different model of hepatic ischemia-reperfusion injury (38). Moreover, our results are in agreement with previous work, which demonstrated that transgenic diabetic mice with overexpression of PRDX4 had reduced NASH scores and a significant improvement of dyslipidemia (39).…”
Section: Discussionsupporting
confidence: 92%
“…2/2 mice linked to a different model of hepatic ischemia-reperfusion injury (38). Moreover, our results are in agreement with previous work, which demonstrated that transgenic diabetic mice with overexpression of PRDX4 had reduced NASH scores and a significant improvement of dyslipidemia (39).…”
Section: Discussionsupporting
confidence: 92%
“…Prx, a diverse and ubiquitous family of antioxidant proteins, includes six mammalian isoforms: Prx1-6 (Rhee et al, 2005). There are already reports demonstrating that Prx3-knockout increased pyrazole-induced liver oxidative damage (Bae et al, 2012), and Prx6-knockout increased ischemia-reperfusion-induced liver injury (Eismann et al, 2009). In the present study, we found that CGA reversed the decreased mRNA expression of Prx1, 2, 3, 5, and 6 induced by AP.…”
Section: Discussionsupporting
confidence: 66%
“…Phospholipase A 2 is a target for regulation by Pin1, which as just discussed, has been reported to be downregulated and showed oxidative dysfunction in the AD brain (65,363). PRX VI has been found to be protective against mitochondrial dysfunction, a feature that pinpoints its effectiveness as an antioxidant (136). PRX VI also plays important roles in cell differentiation and apoptosis, and HNE modification may lead to tau hyperphosphorylation and NFT formation in addition to development of OS.…”
Section: Ead Carbonylated Proteinsmentioning
confidence: 93%